FRI0257 Changes in skeletal muscles in patients with knee joint replacement. (1st June 2001) - Neuen-Jacob, E; Meinhardt, M; Egl, M; Fink, B
Abstract : Background: Knee joint replacement is used as a routine surgical procedure in the treatment of rheumatoid diseases or arthrosis. However, systematical studies on the affected muscles are rare. Objectives: In the present systematic study we analysed the pathological changes in the vastus medialis muscles in 108 patients with rheumatoid arthritis and gonarthrosis who underwent knee joint replacement. The aim of the current study was to examine possible differences in both entities with respect to kind and degree of muscle changes and to the state of innervation/denervation which might be important for the therapeutic effect of the arthroplasty. Methods: Serial cross-cut cryostat sections were stained by H&E and Gomori's trichrome and submitted to routine histochemical preparations including NADH/TR, ATPase after preincubation at pH 4.6 and 9.4, oil-red O, periodic acid Schiff and acid phosphatase. Immunohistochemistry was performed using commercially available monoclonal antibodies (Mab) against neonatal myosin and neural cell adhesion molecule CD56 for the identification of regenerating fibres. In addition, the Mab against HLA-ABC was applied in order to detect the up-regulation of MHC Class I antigen on the muscle fibres. Results: Lipomatosis was striking in the majority of both groups. Regenerating fibres also were detectable in both entities. As a trend, patients with gonarthrosis mainly showed atrophy of type 2 fibres indicating inactivity due to muscle or joint pain. Patients with rheumatoid arthritis commonly revealed atrophy of both type 1 and 2 fibres and fibre type grouping consistent with neurogenic muscular atrophy indicating a systemic disease. Vasculitis was only occasionally detected. In rheumatoid arthritis, however, up-regulation of MHC Class I antigen was regularly seen reflecting the underlying autoimmune disease. A small percentage of cases showed corticoid myopathy with atrophy of type 2 fibres in combination with increased lipid content of type 1 fibres. Conclusion: